Ethno-mathematic Exploration of Historic Site Buildings Medan State Museum - Annisaul Fadilah; Siti Khayroiyah (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
The Indonesian province of Medan is known for its unique culture, which includes architecture, linguistics, music, art, and traditional crafts. Each city has its own distinct identity, and Medan is one of them. The Negeri Medan Museum shares its history with us. This research focuses on introducing spatial structures through the contents of historical buildings, namely the State Museum in Medan. This research aims to describe flat shapes in mathematics learning. The research method used is ethnography, where researchers make observations through observation, documentation and literature studies related to the Medan State Museum. This type of research is qualitative which only describes how the contents of the Medan State Museum Since mathematics requires facts to be precise, understandable, and reliable. From the results of the exploration, it can be concluded that the Medan State Museum is related to the mathematics of geometric shapes consisting of circles, tubes, cubes and rectangles.